Formulasi Sediaan Sabun Mandi Transparan Menggunakan Minyak Kelapa Dengan Penambahan Ekstrak Wortel (Daucus carota L) - Nuraeni Hartih; Dewi Isnaeni; Suherman B (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2023)
This stSudy aimed to formulate transparent bath soap using coconut oil with the addition of carrot extract (Daucus carotaL) and evaluate the physical quality of the soap. This type of research was conducted in laboratory experiments with three variations of coconut oil concentrations namely 20%, 30%, and 40%. Carrots were obtained by blending and then filtered to get the extract. Bath soap was made by the saponification method of NaOH base and the addition of glycerin and coconut oil. The soap formulation was tested organoleptically, foam height, moisture content and pH. The test results proved that coconut oil with the addition of carrot extract can be formulated as a preparation of transparent bath soap with physical quality that meets the Indonesian National Standard (INS).